NORADRENALINE OR DOPAMINE IN SEPTIC SHOCK - A LITERATURE REVIEW - Antoni Liebert; Natalia Klimek; Hanna Wilska; Adam Niedziela; Dominik Domoń; Martyna Kaplińska; Dominika Domanowska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: Septic shock is a common cause of death that is hard to treat and choosing the most effective medication remains a major clinical challenge. The aim of this study is to provide key information about this clinical condition and to compare the drugs most frequently used in the treatment process: noradrenaline and dopamine. Materials and methods: A literature search was conducted using the medical database PubMed and Google Scholar. Articles were retrieved using the keywords: , Noradrenaline” , Dopamine” , Sepsis” , Septic shock” , Hipotension” in appropriate configuration. Results: 8 studies were found with relevant topics. For of these studies were excluded due to lack of information in the articles or discrepancies in their topics. Finally, 4 meta-analyses were systematically analyzed in our work. Conclusions: According to the available medical literature, recommendations and guidelines, the use of Noradrenaline in patients with septic shock is usually the most appropriate choice. However, the choice of Dopamine is also available, especially in patients with bradycardia, but its use can be linked with a higher risk of cardiac complications.